Two new species of Epoligosita Girault (Hymenoptera: Trichogrammatidae) with a key to Indian species - Ikram, Mohsin; Yousuf, Mohammad; Khan, Salman (Zootaxa, 2025)
Two new species of Epoligosita Girault (Hymenoptera: Trichogrammatidae), E. breviclavata Ikram & Yousuf sp. nov. and E. latipennis is Ikram & Yousuf sp. nov. are described from India. A key to Indian species of Epoligosita Girault is also provided.